Security, Trade, and Political Violence - Francesco Amodio; Leonardo Baccini; Michele Di Maio (Institute of Labor Economics (IZA), 2017)
To address security concerns, governments often implement trade barriers and restrictions on the movement of goods and people. These restrictions have negative economic consequences, possibly increasing the supply of political violence. To test this hypothesis, we exploit the restrictions imposed by Israel on imports to the West Bank as a quasi-experiment. In 2008 Israel started enforcing severe restrictions on the import of selected dual-use goods and materials, de facto banning a number of production inputs from entering the West Bank. We show that after 2008 (i) output and wages decrease in those manufacturing sectors that use those materials more intensively as production inputs, (ii) wages decrease in those localities where employment is more concentrated in these sectors, and (iii) episodes of political violence are more likely to occur in these localities. Our calculations suggest these effects account for 18% of the violent political events that occurred in the West Bank from 2008 to 2014.
Keywords: D22; D24; F51; N45; O12; 330; political violence; trade; security